Performance management systems and strategies - Bhattacharyya, Dipak Kumar (Pearson, 2011)
Performance Management Systems and Strategies aims to provide extensive theoretical knowledge with practical overtones for students, and application-based knowledge for professionals to successfully implement performance management systems and strategies. With such comprehensive knowledge and practical skills HR students would be able to develop their capabilities as future manager to manage performance in any organization.